2020
DOI: 10.1002/ece3.6564
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale connectivity, cryptic population structure, and relatedness in Eastern Pacific Olive ridley sea turtles (Lepidochelys olivacea)

Abstract: Endangered species are grouped into genetically discrete populations to direct conservation efforts. Mitochondrial control region (mtCR) haplotypes are used to elucidate deep divergences between populations, as compared to nuclear microsatellites that can detect recent structuring. When prior populations are unknown, it is useful to subject microsatellite data to clustering and/or ordination population inference. Olive ridley sea turtles (Lepidochelys olivacea) are the most abundant sea turtle, yet few studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
(178 reference statements)
0
3
0
Order By: Relevance
“…The microsatellite data were screened for null alleles and genotyping errors (e.g., stuttering) using Micro-Checker (Van Oosterhout et al 2004), and linkage disequilibrium between loci was estimated using Arlequin. Although Silver-Gorges et al (2020) found three of these loci linked in populations from Costa Rica and Mexico, no consistent linkage pattern within populations was detected when analyzing the present worldwide dataset and thus all 15 loci were retained.…”
Section: Microsatellitesmentioning
confidence: 58%
See 2 more Smart Citations
“…The microsatellite data were screened for null alleles and genotyping errors (e.g., stuttering) using Micro-Checker (Van Oosterhout et al 2004), and linkage disequilibrium between loci was estimated using Arlequin. Although Silver-Gorges et al (2020) found three of these loci linked in populations from Costa Rica and Mexico, no consistent linkage pattern within populations was detected when analyzing the present worldwide dataset and thus all 15 loci were retained.…”
Section: Microsatellitesmentioning
confidence: 58%
“…Here we only included longer sequences (> 700 bp) to potentially increase power to resolve population structure. In total, 283 Kemp's ridley (Duchene et al 2012;Frey et al 2014;Reid et al 2019;Frandsen et al 2020) and 340 olive ridley sequences were obtained from published studies (Duchene et al 2012;Plot et al 2012;Jensen et al 2013;Revuelta et al 2015;González-Paredes et al 2017;Campista León et al 2019;Work et al 2019;Adnyana et al 2020;Silver-Gorges et al 2020;Stelfox et al 2020). Several segments from Madagascar and India (Stelfox et al 2020) were excluded because haplotype frequencies were not available, and only publicly accessible haplotypes from Adnyana et al (2020) were included.…”
Section: Mitochondrial Dnamentioning
confidence: 99%
See 1 more Smart Citation